TEMPERAMENT AND LOCUS OF CONTROL AMONG ADOLESCENTS - Dr.C.Saravanaperumal, Dr.H.Deepa (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The present study had been conducted on a sample of 400 students from various Higher Secondary schools of Tuticorin district to find out the relationship between Temperament and Locus of Controlamong adolescent students. Random sampling technique has been used for this study.A self constructedTemperamentQuestionnaire developed by investigatorwas used. The tool contains a set of 40 statements with five alternatives against each statement. Modification of Locus of control scale developed by Nowicki and Strickland (1973) was used.The tool contains a set of 30 statements with two alternatives against each statement representing the two possible ways. YES or NO.The data collected was analyzed and interpreted to draw inference using appropriate statistical methods like mean, standard deviation, Chi Square test and t-test.The results of this study reveal that there is a significant difference between thegender, locality and type of the school in their temperament and locus of control.Chi Square test reveals that there is no significant association between parents Educationand temperament of adolescents.The correlation analysis result shows that there is no significant relationship between temperament and locus of control among adolescents. This may be due to the fact that the adolescents who spend their time only in studies in order to score good marks in the examination, experience a lot of stress, tension, anxiety etc, and they develop a poor temperament. Moreover they attribute success in their life to external circumstances who plan well and distribute their timing to studies, and co-curricular activities etc, are in a better temperament.The present study is temperament and locus of control among adolescents. The investigator is of the opinion that the present study is one of the important aspects to know about the adolescents and how far this helps in their future career.